'Blind time' – current limitations on laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-MC-ICP-MS) for ultra-transient signal isotope ratio analysis and application to individual sub-micron sized uranium particles. Issue 5 (23rd April 2020) - Craig, Grant; Horstwood, Matthew S. A.; Reid, Helen J.; Sharp, Barry L.
Abstract : Gaps in acquisition between integration times for MC-ICP-MS can introduce isotope ratio bias with a mixed detector array. Abstract : The application of laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-MC-ICP-MS) to the isotope ratio analysis of UO x particles has the potential to improve the isotopic determination of these particles when compared to currently utilised ICP-MS techniques. To investigate this a high-speed, integrated ablation cell and dual concentric injector design was tested in the expectation that the resulting increase in signal to noise ratio and sample ion yield would improve the determination of 234 U/ 238 U, 235 U/ 238 U and 236 U/ 238 U for such materials. However, when compared to a slower washout, more established low-volume cell design, the highly transient signals of the new design proved challenging for the mixed detector array of the multi-collector mass spectrometer, introducing a new bias. We describe a major component of this bias, referred to as 'blind time', and model its impact on UO x particle analysis. After accounting for blind time, average precisions for the uranium isotopic composition of sub-micron sized UO x particles using LA-MC-ICP-MS were 3% 1RSD for 235 U/ 238 U and 8% 1RSD for 234 U/ 238 U. When ablating a glass rather than a UO x particle, uncertainties of 1.3% 1RSD for 235 U/ 238 U were achieved for 150 nm equivalent particle sizes using LA-MC-ICP-MS.